2019
DOI: 10.1093/eurpub/ckz186.665
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and sexual behaviors of transgender individuals faced with the risk of STI/HIV in Benin

Abstract: Introduction The issue of sexually transmitted infections (STIs) and Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) cannot be solved without considering the transgender population. This research aims to describe the knowledge, attitudes and sexual behaviors of transgender individuals faced with the risk of STIs and HIV/AIDS in Benin. Methods Transgender individuals were selected by respondent-dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Regarding knowledge about HIV/AIDS among transgender individuals, although a high level of knowledge was observed in 60% of the related studies, Hessou et al's research in Benin reported a 40% low knowledge level (19,23,31). The presence of an acceptable knowledge level in this group underscores the effectiveness of educational and prevention methods, which should be continuously enhanced and expanded (31).…”
Section: Knowledgementioning
confidence: 86%
See 1 more Smart Citation
“…Regarding knowledge about HIV/AIDS among transgender individuals, although a high level of knowledge was observed in 60% of the related studies, Hessou et al's research in Benin reported a 40% low knowledge level (19,23,31). The presence of an acceptable knowledge level in this group underscores the effectiveness of educational and prevention methods, which should be continuously enhanced and expanded (31).…”
Section: Knowledgementioning
confidence: 86%
“…Regarding knowledge about HIV/AIDS among transgender individuals, although a high level of knowledge was observed in 60% of the related studies, Hessou et al's research in Benin reported a 40% low knowledge level (19,23,31). The presence of an acceptable knowledge level in this group underscores the effectiveness of educational and prevention methods, which should be continuously enhanced and expanded (31). To improve transgender individuals' knowledge of HIV/AIDS, our study recommends the development of inclusive sex education, collaboration with transgender-led organizations, ensuring accessible healthcare, enhancing peer support networks, engaging with transgender influencers, tackling systemic barriers, crafting more efficient prevention strategies, and encouraging further research on these groups.…”
Section: Knowledgementioning
confidence: 94%
“…This finding is mostly related to cultural factors and lack of awareness on STIs in traditional societies such as Iran. In India for instance, 88% of transgender people were not familiar with STIs (8) but in Canada 95% of transgender people were familiar with at least three main ways of HIV transmission [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This nding is mostly related to cultural factors and lack of awareness on STIs in traditional societies. In India for instance, 88% of transgender people were not familiar with STIs(8) but in Canada 95% of transgender people were familiar with at least three main ways of HIV transmission [35].…”
Section: Discussionmentioning
confidence: 99%